اسلامی بینکاری کی ترویج میں حائل رکاوٹیں اور ان کا حل: Obstacles in the Promotion of Islamic Banking and their Solution (Khairulummah, 2023)
There is a review of legal, trust-deficit, implementation failure and religious disagreement obstacles in the promotion of Islamic banking. This includes a discussion on legal obstacles for Islamic banking, driving forces of Islamic banking, failure in the implementation of the actions of Islamic banking and making interest rate the standard. It is also stated there that Islamic jurisprudence has given fundamental guidelines in matters of buying and selling, etc. Whether individual or collective, it is necessary to conclude one's affairs while staying within these principles and rules.In the end, there is investigative discussion on Islamic banks' commitment to honesty (financial penalty), mention of obstacles based on blind trust on their lawyers and representatives, customer trust and mistrust, lack of trust of customers on the staff of Islamic banks, objections from scholars, and lack of promotion in Islamic banking. The real reason for disagreement VGin the issue of Islamic banking and detailed arguments from those who are in favor and those who are against have been mentioned.